2011
DOI: 10.1117/12.872347
|View full text |Cite
|
Sign up to set email alerts
|

Visual discomfort with stereo displays: effects of viewing distance and direction of vergence-accommodation conflict

Abstract: Prolonged use of conventional stereo displays causes viewer discomfort and fatigue because of the vergence-accommodation conflict. We used a novel volumetric display to examine how viewing distance and the sign of the vergence-accommodation conflict affect discomfort and fatigue. In the first experiment, we presented a fixed conflict at short, medium, and long viewing distances. We compared subjects’ symptoms in that condition and one in which there was no conflict. We observed more discomfort and fatigue with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 10 publications
3
39
0
Order By: Relevance
“…In terms of the visual discomfort, it is revealed that watching the 3D display clearly caused more visual discomfort than watching the 2D display, regardless of the viewing distance. These results are consistent with those of previous studies [9,33,38,42,[47][48][49].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In terms of the visual discomfort, it is revealed that watching the 3D display clearly caused more visual discomfort than watching the 2D display, regardless of the viewing distance. These results are consistent with those of previous studies [9,33,38,42,[47][48][49].…”
Section: Discussionsupporting
confidence: 94%
“…Shibata et al [33] observed more discomfort and fatigue with a given vergence-accommodation conflict at longer distances. This finding is in agreement with the study conducted by Shibata et al [33], wherein the viewing distance had a significant effect on visual fatigue.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, there are only limited study on the safety evaluation of 3-D vision technology. Scientists from University of California Berkeley [13] built a stereo machine to investigate the unhealthiness. They claim that the physical strain, such as eye fatigue, root in abnormal eye movements; researchers at University of Central Florida [14] claim unknown disparities will cause mental strain, vertigo, and nausea.…”
Section: B Related Workmentioning
confidence: 99%
“…But when stereoscopic 3D simulates an object substantially away from the screen plane, viewers have to converge and focus at different distances. It is well documented that this can cause viewers discomfort and eye fatigue [50][51][52][53] . Such issues can be avoided by ensuring that the conflict is kept within the "comfort zone" 54 , and, ultimately, overcome with better technology, e.g.…”
Section: What Is Stereoscopic Vision Good For In Art?mentioning
confidence: 99%